A medical cost estimation with fuzzy neural network of acute hepatitis patients in emergency room. Issue 1 (October 2015) - Kuo, R.J.; Cheng, W.C.; Lien, W.C.; Yang, T.J.
Highlights FNN is employed to develop the cost forecasting model for acute hepatitis patients in emergency room. The FNN model can provide more accurate forecast than SVR and ANN. Unlike SVR and ANN, FNN can also provide fuzzy IF–THEN rules for interpretation.